The Effect of Work Discipline and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable in PT. PGAS Solution Area Riau - Ramadhan, Aldestu; Neldi, Mondra; Putra, Ramdani Bayu (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This study aims to determine the influence of discipline and work motivation on employee performance with job satisfaction as an intervening variable in PT. PGAS Solution Area Riau. This research was carried out with a quantitative approach with a data collection method through surveys and distributing questionnaires, with a sample of 60 respondents using the random sampling method, namely the population has the same opportunity to be selected as a sample. Data collection was carried out using a questionnaire. The analysis used is Structural Equation Modeling (SEM) analysis with Partial Least Square (PLS). For hypothesis tests, they are used, namely Path Coeficient, which is a test that is carried out to see the direct influence and Indirect Effect is a test that aims to see the indirect influence. The results of data analysis showed that there was a positive and significant influence between work discipline and job satisfaction. There was a positive and significant influence between work motivation and job satisfaction. There is a positive and significant influence between work discipline and employee performance. There is a negative and insignificant influence between work motivation and performance at PT. PGAS Solution Area Riau.